Incidence of Human Scabies in Duhok Province, Kurdistan Region/ Iraq - Mero, Wijdan M.S.; Hassan, Haliz Kh. (Science Journal of University of Zakho, 2014)
This study was conducted in Duhok city to evaluate the incidence of scabies among outpatients from both sexes and different ages from one year to over 60 years visited the dermatology clinic in Azadi Teaching Hospital from September 2012 to April 2013. Other factors like residency, educational levels, number of family members, source of contact and clinical manifestations were also studied. Scabies was diagnosed in 522 (5.5%) out of 9450. Higher rates (20.11% and 20.5%) of scabies were observed among age groups 1-10 and 11-20 years, respectively, then the rate decreased with the increase in the age. Female patients had higher frequency than males (53.06% and 46.94%, respectively). Moreover, the highest rate (60.53%) was found among illiterates patients and decreased with the increase in the level of education. The urban and rural residents showed high prevalence rates (37.16 and 34.86%) as compared to suburban (27.98%). About half of the cases occurred from household contact (50.98%) and 34.67% acquired from outside homes, 13.78% from unknown sources and only 0.57% from contact with prisoners. The clinical findings, 91.57% of the patients suffered from itching that turned to secondary bacterial infection, the disease was generalized in 53.06%, localized in 29.12% of the cases affecting hands, fingers and legs, and in 17.82% of the cases affected their abdomen, back and under arms. According to disease duration 31.42% of the patients seek medical attention during the first week of having the symptoms, 24.90 % during the second week, 17.63% during the fourth week and 26.05 % delayed medical consultation for more than a month. Regarding living conditions, 21.83% of the patients lived in a house with less than five persons and high standard of living, while 78.17% of the patients lived in a very crowded house with 6 to 18 persons.